2014
DOI: 10.1111/jphd.12055
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of opioid and nonopioid analgesics for dental care in emergency departments: Findings from the National Hospital Ambulatory Medical Care Survey

Abstract: Objective The aim of this study was to examine trends and associated factors in the prescription of opioid analgesics, non-opioid analgesics, opioid and non-opioid analgesic combinations and no analgesics by emergency physicians for nontraumatic dental condition (NTDC)-related visits. Our secondary aim was to investigate whether race/ethnicity is a possible predictor of receiving a prescription for either type of medication for NTDC visits in emergency departments (EDs) after adjustment for potential covariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 32 publications
1
35
2
1
Order By: Relevance
“…The single most common diagnosis among all users was “dental disorder not otherwise specified.” This diagnosis may reflect the inability of clinicians who are not dentists to make precise dental diagnoses in the ED. Among high users, this vague diagnosis combined with fragmentation of visits raises concern that some of these individuals may have visited multiple EDs primarily to obtain painkillers or other drugs . While our data are not sufficiently detailed to be definitive on this point, we suggest that improved coordination between medical and dental services could play a large role in the identification and care management of individuals who are engaging in these behaviors.…”
Section: Discussionmentioning
confidence: 82%
“…The single most common diagnosis among all users was “dental disorder not otherwise specified.” This diagnosis may reflect the inability of clinicians who are not dentists to make precise dental diagnoses in the ED. Among high users, this vague diagnosis combined with fragmentation of visits raises concern that some of these individuals may have visited multiple EDs primarily to obtain painkillers or other drugs . While our data are not sufficiently detailed to be definitive on this point, we suggest that improved coordination between medical and dental services could play a large role in the identification and care management of individuals who are engaging in these behaviors.…”
Section: Discussionmentioning
confidence: 82%
“…To the best of our knowledge, only one study has attempted to document emergency physician prescribing practices of opioid analgesics and opioid combinations for nontraumatic dental conditions (Okunseri et al, 2014). In addition, there is no study based on either a convenience or a population-based representative sample that has specifically examined the different opioids prescribed in emergency departments for NTDC visits.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that there has been a substantial increase in prescribing pain medications by non-dental providers (6,8). In 2010, there were approximately 129.8 million emergency department visits, and it is estimated that dentofacial emergencies represent between 0.3% and 4.0% of the overall patient emergency department workload (9,7,5). Given these trends, emergency department providers should be equipped to diagnose, provide basic treatment, and ensure appropriate follow-up care for dental problems.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving limited and focused dental care in this setting could potentially decrease the need for prescribed opioid analgesics. However, the literature suggests that emergency department physicians do not feel confident in managing dentofacial emergencies and are interested in additional education (9,10,7). These data suggest that emergency department providers may require more extensive training in alternative treatment procedures such as local anesthetic administration, nerve blocks or immobilization in order to respond to emergency department visits of dentofacial origin.…”
Section: Introductionmentioning
confidence: 99%